ANALISIS KONTRIBUSI SEKTOR PERTANIAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO KABUPATEN MINAHASA - Liow-Laloan, Vini; Rumagit, Merry C. N.; Sinolungan, Alzefin (Jurnal Equilibrium, 2023)
The purpose of the study is to estimate the Gross Regional Domestic Product (GRDP) contribution of the agriculture sector to Minahasa Regency over the last eight years (2015-2022). Utilizing secondary data from the Central Statistics Agency (BPS) of Minahasa Regency, the quantitative research methodology was applied. To gauge how much the agriculture sector affects GDP, contribution analysis is utilized. Additionally, this research analyzes the area economy using Location Quotient (LQ) Analysis techniques to pinpoint Base or Leading Sectors. This approach contrasts the economic contributions of various sectors and utilizes LQ criteria to categorize them as basic or non-base. The findings revealed that of the seven agricultural subsectors now in existence, the poultry farming sub-sector made one of the highest contributions to GDP notwithstanding variations. In this context, the Poultry Farming Subsector can be considered as a leading sector in the agricultural sector in Minahasa Regency. The use of the LQ method also provides an understanding of the Base or Featured Sector specialization level. By comparing LQ from different sectors, researchers can identify sectors that have an important role in the regional economy. This research provides a deeper understanding of the Contribution of the Agricultural Sector and the identification of Base Sectors in Minahasa Regency. The results of this research can be the basis for policy making and economic development strategies in the region.Ã‚Â  Ã‚Â